Distance education: historical overview and current practices in Malaysian higher education - Abd Rahim, Nur Aira (Human Resource Management Academic Research Society, 2018)
Distance education is a dynamic and complex area of inquiry. Ever since its early conception, distance education has undergone various theoretical development to reflect the ongoing changes and practices in the field. In particular, the field has vastly been influenced by the advent of various technologies in communication and information delivery systems since the start of 21st century. The first part of this article addressed the key historical developments of distance education in higher education. Next, various definitions of distance education and its related terms were presented. This article also discusses the overview of current practices of distance education in Malaysian higher education.